On the question of the rights and obligations of a woman and a man who live with one family without registration of marriage - Luchkovskyi, Valentyn (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The scientific article examines the content of the rights and responsibilities of a woman and a man living in the same family without registration of marriage (de facto marriage) on the basis of doctrinal sources and current family law. As a result of scientific research, the author concluded that the rights arising from the actual marital relationship in the family law of the de facto spouse are generally similar to the rights of the spouses in a registered marriage, but only in part of the common property acquired in the de facto marriage, joint rights as parents over the child, the right to maintenance and adoption. An agreement between a woman and a man living in the same family but not in a registered marriage with each other or in any other marriage, regarding the definition of their property rights and obligations and the legal regime of jointly acquired property, may provide for another legal regime of such property, in particular in the form of joint partial ownership or personal private ownership of the actual spouse. The de facto spouse has the right to enter into an agreement on maintenance in the actual marital relationship, in which to expand the list of grounds for the occurrence of maintenance obligations, as well as to determine in more detail the procedure for their performance by the de facto spouses. Also, the de facto spouse has personal inalienable rights similar to the rights and responsibilities of the spouses in a registered marriage , including: the right to motherhood and fatherhood, respect for their individuality, physical and spiritual development, education, manifestation of their abilities, creating conditions for work and leisure, the division of responsibilities and joint resolution of family life, freedom and personal integrity, the duty to care for the family, but formally they are not defined at the level of family law as such that belong to the actual spouse.. At the same time, the de facto spouse has the right to change the surname on general grounds, and not in the manner prescribed by the Family Code of Ukraine.